ELEMENTS OF TRADITIONAL CULTURE AS FACTORS OF RETAINING THE COLLECTIVE MEMORY AND ETHNIC IDENTITY IN DIASPORAS: ON THE CASE OF ADYGHE DIASPORA IN THE COUNTRIES OF THE MIDDLE EAST - Kudaeva, Svetlana Grigor'evna (History, Archeology and Ethnography of the Caucasus, 2021)
The issue under consideration is conditioned by the current state of the Adyghe (Circassian) ethnos, when a diaspora, in terms of its quantitative composition, significantly exceeds the number of those living in their historical homeland. Nowadays, the Circassian people are concentrated in the countries of the Middle East. This was a result of the Caucasian War, when a significant number of Adyghe people had to leave their homeland and move to the territories of the Ottoman Empire. In regard to this issue, the problems related to the peculiarities of the formation, development and current state of the Adyghe (Circassian) diaspora are highlighted. The paper considers the Adyghe diaspora in the context of the criteria that determine the diasporality of ethnic dispersal. The author summarizes the results of studies on typology of diasporas, during which characteristic for the Circassian diaspora features have been identified. The author concludes that the Adyghe diaspora can be attributed to a single typological family, as the classical diasporas. This allows for better understanding of where the issue in question is placed in this hierarchy. The very maintaining of the collective memory is considered a crucial, fundamental indication of diasporality. The author attempts to study the issue with the consideration of influence of elements of traditional culture of Adyghe people, such as the Nart Sagas, Adyghe etiquette and ethics in regards to retaining the historical memory and ethnic identity. The methodological aspect of the study includes the academic principles of research, historicism, objectivity, as well as retrospective and historic-typological methods, and methods of concrete analysis. The theoretical aspect of the research is based on opinions of prominent ethnologists and ethnosociologists. During the research, we have come to the conclusion that in the century and a half experience of its existence, the Adyghe diaspora has managed to demonstrate a unique example of preservation of the collective memory and ethnic identity.